Children's use of Bahasa Indonesia in Jakarta kindergartens - Kushartanti, Bernadette; Van de Velde, Hans; Everaert, Martin (UI Scholars Hub, 2015)
At a very young age children living in Jakarta use both Colloquial Jakarta Indonesia and Bahasa Indonesia. The children's first and most used language is Colloquial Jakarta Indonesia. In the formal school setting Bahasa Indonesia is frequently used and stimulated on a daily basis, and the learning process of Bahasa Indonesia is accelerated. The question addressed in this article is: how do these children choose from their repertoire of language varieties at this stage of language development? In our study 63 children (aged three to five), were interviewed in a formal and an informal situation in three playgroups and kindergartens. This study shows that even in the preschool setting, young children are already developing their sociolinguistic competence, knowing when to choose which language variety.